Pelaksanaan Pelayanan Neonatal Berdasarkan Standar Pelayanan Minimal Kesehatan Bayi Baru Lahir di Puskesmas Dukuhseti Kabupaten Pati - Arum Rohana; Ayun Sriatmi; Rani Tyas Budiyanti (Jurnal Kesehatan Masyarakat (Undip), 2020)
The Minimum Service Standards (MSS) are a national strategic program and the Puskesmas are the leading unit in efforts to achieve the MSS targets. Pati Regency occupies the top 6 highest infant mortality cases in the province of Central Java in 2018 and the highest number of cases is in the Dukuhseti Primary Health Center (PHC). Dukuhseti PHC is a BLUD PHC that must apply MSS including newborn health services, but the implementation is not optimal as indicated by the coverage of neonatal visits that have not reached the target. The study aims to analyze the implementation of health MSS in newborn health services in Dukuhseti PHC. This research is a qualitative research with in-depth interviews and observations using content description analysis. The results showed that the implementation of SPM in newborn health services was constrained in the implementation of KN2 and KN3, neonatal care counseling, health examination with MTBM, and handling neonatal referral cases. That was because most of the midwives had not received MTBM training, there was no budgeting for health training, double jobs because midwife HR at the PHC was lacking, the targets used a lot of real data, recording and reporting were not in order, supervision from the leadership was not optimal, difficulties in finding health facilities referral, and there is no strict sanction from the District Health Office (DHO). PHC are expected to be able to budget funds for training for health workers, provide guidance for better coordination, fix information systems and referral applications by implementing an online-based Integrated Referral System. The DHO is expected to be able to improve supervision by implementing more systematic evaluations and reinforcing sanctions so that the implementation of MSS in newborn health services runs optimally.